Basic approaches to the choice of material for working blades of the last stages of the LPC of powerful steam turbines - Slaston, L.O.; Ishchenko, M.G.; Sherfedinov, R.B.; Alyokhina, S.V. (Вопросы атомной науки и техники, 2020)
The paper outlines the need for a comprehensive analysis and selection of steels for the working blades of the last stages of low pressure cylinders (LPC) of high-power steam turbines. The authors reviewed the criteria and existing technical requirements for the materials of the working blades. The analysis of various grades of steels for low-pressure cylinder blades was carried out taking into account the experience of their production at JSC “Turboatom”. The proposals on the use of materials of working blades with a large length of the active part are given, as well as ways for further research are outlined. Вказано на необхідність проведення комплексного аналізу і вибору сталей для робочих лопаток останніх ступенів циліндрів низького тиску (ЦНТ) парових турбін великої потужності. Авторами розглянуті критерії та існуючі технічні вимоги до матеріалів робочих лопаток. Проведено аналіз різних марок сталей для лопаток ЦНТ з урахуванням досвіду їх виробництва в АТ «Турбоатом». Надано пропозиції щодо використання матеріалів робочих лопаток з великою довжиною активної частини, а також намічені шляхи проведення подальших досліджень. Обозначена необходимость проведения комплексного анализа и выбора сталей для рабочих лопаток последних ступеней цилиндров низкого давления (ЦНД) паровых турбин большой мощности. Авторами рассмотрены критерии и существующие технические требования к материалам рабочих лопаток. Проведен анализ различных марок сталей для лопаток ЦНД с учетом опыта их производства в АО «Турбоатом». Даны предложения по использованию материалов рабочих лопаток с большой длиной активной части, а также намечены пути проведения дальнейших исследований.